Evaluating bone mineral density in osteoporotic vertebral compression fractures: the clinical utility of anterior column Hounsfield units - Chen, Jiabao; Zheng, Han; Li, Haotian; Yu, Qingsong; Li, Yanhong; An, Huangda; Ma, Lei (Frontiers in Endocrinology, 2025)
Study DesignRetrospective radiological analysis.ObjectiveThis study aimed to evaluate the clinical utility of anterior column Hounsfield units (HU) in assessing bone mineral density (BMD) in patients with osteoporotic vertebral compression fractures (OVCFs) and to investigate its potential advantages over traditional measurement methods.MethodIn this retrospective study, we analyzed data from 106 patients with acute OVCFs treated between January 2020 and June 2024. Inclusion criteria encompassed single-segment fractures from T10 to L2, with clear imaging results. HU values were measured from computed tomography (CT) scans, specifically targeting the anterior column of the vertebral body. Interobserver reliability was assessed via intraclass correlation coefficients (ICCs). Correlations between HU values, dual-energy X-ray absorptiometry (DEXA) results, and vertebral compression degrees were analyzed using Pearson correlation and receiver operating characteristic (ROC) curve analysis.ResultsThe average HU values were significantly lower in the anterior column (50.39 ± 21.62 HU) compared to the middle column (63.12 ± 25.14 HU). The anterior column HU values showed a strong positive correlation with DEXA T-scores (r = 0.643) and BMD (r = 0.656). The degree of vertebral compression also correlated positively with both HU values and DEXA results, with the anterior column HU demonstrating the highest correlation (r = 0.727). ROC analysis indicated that the anterior column HU value had the largest area under the curve (AUC = 0.913) for predicting severe OVCFs, with an optimal cutoff of 59.07 HU.ConclusionThe anterior column HU value serves as a superior predictor of BMD in patients with OVCFs compared to traditional methods. This study highlights the potential of using anterior column HU measurements to guide clinical decision-making regarding treatment options for OVCF patients, suggesting a shift towards more nuanced assessment strategies in osteoporosis management. Further research with larger sample sizes is warranted to validate these findings and explore the comprehensive application of HU values in osteoporosis evaluation.